Foreshadowing Elements in Shakespeare's and Baz Luhrmann's Romeo and Juliet - Lestyán Viola (2004)
In 1996, the Australian director Baz Luhrmann made the latest adaptation of William Shakespeare's Romeo and Juliet. The aim of my paper is to point out the differences and the similarities between the film by Baz Lurhmann and Shakespeare's original play concerning the water image. The main leading focus of my paper is on the foreshadowing elements. In the drama, we can see that the tragic end is emphasised by the device of misgivings. If we examine the film however, we find that the foreshadowing element of the sad end is water. The scenes from the film that I will discuss in the second part of my paper are all contain the element of water. At the end of my paper, I come to the conclusion that apart from the foretelling role, water might also mean death and Juliet herself.